Similarity search and applications : 6th International Conference, SISAP 2013, A Coruña, Spain, October 2-4, 2013, Proceedings - Pedreira, Oscar; Zezula, Pavel; Brisaboa, Nieves (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Similarity Search and Applications, SISAP 2013, held in A Coruña, Spain, in October 2013. The 19 full papers, 6 short papers and 2 demo papers, presented were carefully reviewed and selected from 44 submissions. The papers are organized in topical sections on new scenarios and approaches; improving similarity search methods and techniques; metrics and evaluation; applications and specific domains; and implementation and engineering solutions.